2000
DOI: 10.1063/1.1288153
|View full text |Cite
|
Sign up to set email alerts
|

Magnetohydrodynamic waves in a homogeneous plasma convected uniformly at relativistic speed

Abstract: The plasma in several physical situations such as movement of electrons along the geomagnetic field lines in the magnetosphere, the movement of the ionosphere, propagation of cosmic rays, etc., can be appropriately simulated by a drifting relativistic model. Keeping this in view, a general dispersion relation for magnetohydrodynamic (MHD) waves has been derived in a laboratory stationary coordinate system with respect to which plasma is drifting with a velocity which need not be small compared with the speed o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…x−z plane (plotted is thus v ph = v ph n by varying n in x−z over 2π), and it should be noted that the suppressed third dimension is no longer a mere revolution about some axis as soon as the velocity v is not aligned with B. For the particular case where v is aligned with B (the case in the study by Kalra and Gebretsadkan 14 ), it is merely to be rotated about the z-axis. In any case, the visual representation of the phase diagram is arguably the most intuitive way to illustrate the combined effects of the inherent anisotropic nature of MHD wave propagation (even in uniform media), with the added complexity brought in by relativistic wave aberration.…”
Section: B Lab Frame Expressionsmentioning
confidence: 99%
See 3 more Smart Citations
“…x−z plane (plotted is thus v ph = v ph n by varying n in x−z over 2π), and it should be noted that the suppressed third dimension is no longer a mere revolution about some axis as soon as the velocity v is not aligned with B. For the particular case where v is aligned with B (the case in the study by Kalra and Gebretsadkan 14 ), it is merely to be rotated about the z-axis. In any case, the visual representation of the phase diagram is arguably the most intuitive way to illustrate the combined effects of the inherent anisotropic nature of MHD wave propagation (even in uniform media), with the added complexity brought in by relativistic wave aberration.…”
Section: B Lab Frame Expressionsmentioning
confidence: 99%
“…This can indeed be done by linearizing about a moving ͑i.e., stationary͒ uniform plasma, as was pursued in Kalra and Gebretsadkan 14 for the special case where the movement v was aligned with the uniform field B, but this is by far the most algebraically complex means to do so. It must be realized that the more general result ͑for arbitrary orientation between v and B͒ was already given in the textbook by Lichnerowicz 2 and Anile, 3 obtained from the more appropriate covariant form ͑i.e., valid in any reference frame͒.…”
Section: B Lab Frame Expressionsmentioning
confidence: 99%
See 2 more Smart Citations
“…[1,2]), the detailed analysis of HMHD waves was not conducted until Hameiri et al revealed that phase and group diagrams are deformed by the Hall effect [25]. In addition to the non-relativistic models, the dispersion relation for relativistic ideal MHD has been studied [17,18,26,27]. Keppens and Meliani drew phase and group diagrams of the relativistic MHD showing that there is no qualitative difference between non-relativistic and relativistic diagrams in a fluid rest frame, except for the presence of the light limit [27].…”
Section: Introductionmentioning
confidence: 99%